Paediatric respiratory disease an atlas of investigation and management - Bush, Andrew, 1954 April 24-; Davies, Jane C. (Clinical Pub. ; Distributed in USA and Canada by Clinical Pub., 2011)
Comprehensive guide to parenchymal respiratory disease in children. Deascribes congenital disorders, disease in neonates, malignant, neuromuscular, interstitial diseases, scleroderma, granulatomas, mucopolsaccharidoses, sickle-cell disease, and rare neoplasm. Suitable for specialists in respiratory medicine, paediatricians, doctors in training.